A Phenotypic Compound Screening Assay for Lysosomal Storage Diseases. (January 2014) - Xu, Miao; Liu, Ke; Swaroop, Manju; Sun, Wei; Dehdashti, Seameen J.; McKew, John C.; Zheng, Wei
The lysosome is a vital cellular organelle that primarily functions as a recycling center for breaking down unwanted macromolecules through a series of hydrolases. Functional deficiencies in lysosomal proteins due to genetic mutations have been found in more than 50 lysosomal storage diseases that exhibit characteristic lipid/macromolecule accumulation and enlarged lysosomes. Recently, the lysosome has emerged as a new therapeutic target for drug development for the treatment of lysosomal storage diseases. However, a suitable assay for compound screening against the diseased lysosomes is currently unavailable. We have developed a Lysotracker staining assay that measures the enlarged lysosomes in patient-derived cells using both fluorescence intensity readout and fluorescence microscopic measurement. This phenotypic assay has been tested in patient cells obtained from several lysosomal storage diseases and validated using a known compound, methyl-β-cyclodextrin, in primary fibroblast cells derived from Niemann Pick C disease patients. The results demonstrate that the Lysotracker assay can be used in compound screening for the identification of lead compounds that are capable of reducing enlarged lysosomes for drug development.